International Continence Society (ICS) report on the terminology for nocturia and nocturnal lower urinary tract function. Issue 2 (15th January 2019) - Hashim, Hashim; Blanker, Marco H.; Drake, Marcus J.; Djurhuus, Jens Christian; Meijlink, Jane; Morris, Vikky; Petros, Peter; Wen, Jian Guo; Wein, Alan
Abstract : Introduction: The terminology for nocturia and nocturnal lower urinary tract function is reviewed and updated in a clinically and practically‐based consensus report. Methods: This report has been created by a Working Group under the auspices and guidelines of the International Continence Society (ICS) Standardisation Steering Committee (SSC). All relevant definitions were updated on the basis of research over the last 16 years since the publication of the first nocturia standardization document in 2002. An extensive process of 16 rounds of internal and external reviews was involved to examine each definition exhaustively, with decision‐making by collective opinion (consensus). Results: A clinically‐based terminology report for nocturia and nocturnal lower urinary tract function, encompassing five key definitions divided into signs and symptoms has been developed. Clarity and user‐friendliness have been key aims to make it interpretable by healthcare professionals and allied healthcare practitioners involved in the care of individuals with nocturnal lower urinary tract function. Conclusion: A consensus‐based terminology report for nocturia and nocturnal lower urinary tract function has been produced to aid clinical practice and research.